Design of an Integrated Temporary Storage for Hazardous and Toxic Material Wastes 4.0 Case Study in The Department of Industrial Chemical Engineering - Farida Rahmawati; Purwodarmianto; Slamet Hariono; Muhammad Dadang (IPTEK The Journal of Engineering, 2024)
The Department of Industrial Chemical Engineering is one of the departments within the Faculty of Vocation at Institut Sepuluh Nopember Surabaya (ITS). It has four laboratories. The activities conducted in these laboratories, both in terms of practical work and research, generate hazardous and toxic waste that should be stored in a temporary waste storage facility. Temporary storage is crucial for safely containing hazardous and toxic Hazardous waste until it can be properly processed, disposed of, or transported to a permanent storage location. The primary goals of this facility are containment, separation, safety, and compliance with environmental regulations. The design and features of the facility play a crucial role in ensuring the effectiveness of temporary storage. Secondary containment structures, chemical compatibility measures, ventilation systems, safety protocols, and emergency response equipment are the primary components of this facility. These elements work together to prevent leaks, control chemical reactions, disperse hazardous vapours, maintain safety, and enable rapid emergency response. This research provides knowledge on the design of temporary storage facilities for hazardous and toxic materials, with technical specifications following regulations. Effective temporary storage management can protect human health and the environment and promote sustainable waste management practices.